The Correlation of Parents' Social Support with Student Achievement in Aqidah Akhlak Subjects - Jusmeli Hartati; Tumin Tumin (Al-Hayat Al-Istiqomah Foundation collab with Letiges, 2021)
This study aims to describe parents’ social support with learning achievement in the subject of akidah akhlak (moral theology) at MTsN (Islamic Junior High School) 3 Sijunjung, as well as to see the correlation between parents’ social support and learning achievement in the subject of akidah akhlak in students at MTsN 3 Sijunjung. This research is a correlation study using a quantitative approach with descriptive methods. Data were analyzed using descriptive statistics in the SPSS version 21 program and Pearson Product Moment Correlation (r). This study used a quantitative research approach with data collection using observation, questionnaires, and documentation. The research subjects were 138 students of MTsN 3 Sijunjung who were in grade VIII. The results showed that the average value of parents’ social support was 66.1667, which means that parents’ social support was at the moderate category level. At the same time, the average value of learning achievement in akidah akhlak subject is 69.8188 at a moderate level. The results show that the correlation coefficient was 0.428. This means that the strength of the correlation is at a moderate level. There is a significant correlation between parents’ social support and learning achievement in akidah aklak subject because the very significant correlation value is 0.000. This result shows that Ha is accepted and Ho is rejected. So that the greater the parents’ social support, the better the learning achievement of the students of MTsN 3 Sijunjung. It is because the results of the coefficient distribution are positive. The finding in this study is that the greater the parents’ social support, the better the student’s achievement in akidah aklak subject.